Pelatihan Al-Banjari Guna Meningkatkan Karakter Islami Di Organisasi Ansor Desa Jambangan Sidoarjo: Pelatihan Al-Banjari Berbasis Abcd Untuk Penguatan Karakter Islami Generasi Muda Di Organisasi Ansor Desa Jambangan Sidoarjo - Mochammad Busyro Nurul Furqon; Solchan Ghozali (Journal of Research and Community Service, 2025)
Religious arts-based training is an effective alternative for developing Islamic character among the younger generation. However, in many village-level religious organizations, such activities are still ceremonial and not systematically managed. This program aims to strengthen the Islamic character of the younger generation through Al-Banjari training based on the Asset-Based Community Development (ABCD) approach. The program was implemented using a community-based experiential learning approach that emphasizes active participant involvement. A total of 25 young Ansor members participated in a series of activities over four weeks, covering the preparation, implementation, and evaluation stages. Data were collected through participatory observation, reflective interviews, character questionnaires, and photo and video documentation. Data analysis was conducted using descriptive qualitative methods using an interactive model. The results of the activity showed significant improvements in rebana playing skills, rhythmic cohesion, and participants' ability to understand the spiritual meaning of shalawat chants. Participant attendance increased to 95% during the training, reflecting growing discipline and responsibility. Furthermore, participants formed an independent Ansor Bershalawat hadrah group that actively performs at village religious events, signifying the program's sustainability and strengthening of Islamic brotherhood. This activity has proven effective as a medium for developing Islamic character based on religious arts. It not only develops Islamic arts skills but also instills the values ​​of discipline, cooperation, responsibility, and spirituality within the real context of a religious organization. This program can serve as a model for community-based Islamic character development at the village level, while simultaneously strengthening moderate Islamic cultural preaching (wasathiyah). The experiential learning approach implemented can be replicated by educational institutions and other religious organizations to develop a young generation that is religious, creative, and virtuous.